PERUBAHAN FUNGSI GELOMBANG ELEKTRON PADA MULTIPLE SCATTERING UNTUK SUDUT HAMBUR NOL - Guswantoro, Taat; Nur, Muhammad; Gunawan, Vincencius (BERKALA FISIKA, 2014)
Multiple scattering in the plasma present doe to movement of charged particle influenced by Coulomb interaction between charged particles in the plasma. Research on multiple scattering among influences of effective field on the multiple scattering, lost energy due to scattering processes, the aims of this study are to determine the scattered wave function, multiple scattering cross-sections and scattered electron energy. The understanding of the electron scattering in the plasma in this study using the optical approximation that is application of wave properties of electron. The calculation ofÂ  scattered wave function is using first Born approximation, by taking the scattering potential energy is the summary of potential energy of electron by interaction with each ions that present in the plasma sphere. Electron wave function after scattered is changes, though the direction is same with the direction of initial electron coming, presence a reduction in amplitude as a function of the distance the wave trajectory. Keywords: Multiple Scattering, Plasma, Born approximation.